Are early stage investors biased against women? - Ewens, Michael; Townsend, Richard R. (Journal of Financial Economics, 2020)
We study whether early stage investors have gender biases using a proprietary data set from AngelList that allows us to observe private interactions between investors and fundraising startups. We find that male investors express less interest in female entrepreneurs compared to observably similar male entrepreneurs. In contrast, female investors express more interest in female entrepreneurs. These findings do not appear to be driven by within-gender screening/monitoring advantages or gender differences in risk preferences. Moreover, the male-led startups that male investors express interest in do not outperform the female-led startups they express interest in—they underperform. Overall, the evidence is consistent with gender biases.